Mathematical Modeling of Tourism Development. An Application to Albanian Tourism - KOSOVA, Robert; SINAJ, Valentina (Journal of Environmental Management and Tourism, 2021)
The article contains a comprehensive study of tourist arrivals in Albania in the years 1994 to 2020. During this period, the trend of tourism development has been studied, using the widely approved concept of Tourist Area Cycle Theory (TALC).  During these years, the number of tourists has been growing rapidly, and, the touristic sites of Albania have been transformed to serve touristic purposes, especially the coastline. Recently the geographic touristic map has been enlarged to the mountain and rural areas, touristic villages, and cultural, archaeological, historical tourism. The dynamics of tourism development have been studied by many researchers, academics, and institutions to provide a complete and clear picture of the history and predict the future of the tourism industry. Econometric, mathematical or mixed models are applied to fit the tourism development and they have been helpful and have served the purpose. The model we have used to analyze the arrivals in Albania is the Logistical and the Gompertz model, largely used to estimate growth under limited resources. The tourist arrivals, i.e., the number of tourists entering the destination country have been considered as the most important variable to describe the tourism development. Several useful software is mostly used to fit the historical data and predict future arrivals such as Stata, Lab fit, Curve Expert, Spss, etc. In our case the Stata software to run the data provided for this article. The data for this article are provided from INSTAT (National Institute of Statistics), ( http://www.instat.gov.al/ ) and other National  Institutions such as the Ministry of Tourism and Environment of Albania, ( https://turizmi.gov.al/ ), and several International Institutional such as the World Bank, ( https://data.worldbank.org/indicator/ST.INT.ARVL?locations=AL ), World Tourism Organization, ( https://www.unwto.org/statistic/basic-tourism-statistics ). The data, together with the growing numbers of tourists show the significant impact of tourism on the economic development of the country, income, contribution to the Gross Domestic Product (GDP), employment, etc.